MEDIA AUDIO VISUAL SEBAGAI MEDIA PENINGKATAN KETERAMPILAN MENULIS TEKS DESKRIPSI DI SMP NEGERI 3 KOTA BOGOR - Nurjanah .; Yudhie Suchyadi (Fakultas Keguruan dan Ilmu Pendidikan Universitas Pakuan, 2020)
THE APPLYING AUDIO-VISUAL MEDIA TO THE IMPROVEMENT OF WRITING SKILL OF DESCRIPTIVE TEXT IN JUNIOR HIGH SCHOOL (SMP NEGERI 3 KOTA BOGOR)The research aims to find out the improvement of VII grade students of SMP Negeri 3 Kota Bogor in writing descriptive essays using audio visual media. The method used in this study is the Classroom Action Research (CAR) method. Data collection was carried out by the method of observation, field notes, tests, interviews, and student questionnaires. This research was conducted in two cycles. One cycle consists of four stages, namely: action planning, action implementation, observation, and reflection. The results showed an increase in the average value of students' understanding of writing descriptions through audio-visual media. During the first cycle, the average student score was 70.86 or are at the level of completeness 73.12%. While during the second cycle, the average student score was 79.89 or 90.74% completeness level. An increase also occurred in the motivation and activeness of students in learning and in completing assignments.